Efficient solar heater box for control of Tribolium castaneum (Herbst) (Coleoptera: Tenebrionidae) on cocoa beans - Abdullahi, Gambo (2017)
Insect infestation is one of the factors that is normally considered during the grading of cocoa beans. Tribolium castaneum (Herbst) is one of the insect pests that has been consistently found attacking cocoa beans in Malaysia. Solar heater boxes of smaller sizes have been found to be effective in collection and retention of solar radiation as heat at levels lethal to stored product arthropod pest inside the box. The need to determine the damage potential of T. castaneum on cocoa beans and to develop solar heater box that could handle large amount of commodity lead to this study with the following objectives: (1 ) to determine the damage potential of T. castaneum on Malaysia cocoa beans (2) to construct a solar heater boxes of different sizes and assess their solar heat-trapping capacity as well as the effect of quantity of cocoa beans and exposure time on the heat trapping ability of the solar heater box (3) to evaluate the effect of solar heat trapped by best performing solar heater box on the life stages of T. castaneum (4) to examine the effect of solar heat treatment at different exposure times in cardboard solar heater box on the quality attributes of cocoa beans. Damage potentials of T. castaneum on cocoa beans were investigated under laboratory conditions by focusing on the effect of different initial population densities (0, 10, 20 and 30) at five post infestation storage times (30, 60, 90, 120 and 150 days) as well as their interactions on final adult population density, percentage of insect damaged cocoa beans, percentage of weight loss, and weight of insect feeding residues. Both factors and the associated interaction had a highly significant (P<0.01) effects on all the response variables assessed. The highest mean final population density of 129.67±4.60 was recorded in samples infested with 30 adults and stored for 150 d, while the least mean adult population density of 10.81±0.54 were recorded on samples infested with 10 adults and stored for 30 days. The highest percentage (50.97±1.21%) insect damaged cocoa beans were recorded in samples infested with 30 individuals, while the least mean percentage (16.88±1.26%) insect damaged cocoa beans were also recorded on samples infested with the lowest 10 adults and stored for 30 days. Similar trends of means were recorded for all the remaining other response variables. Correlations between variables were significant and positive.